KECAKAPAN BERBAHASA INDONESIA DALAM NARASI BRANDING DIGITAL UMKM: ANTARA IDENTITAS LOKAL DAN TUNTUTAN PASAR GLOBAL - Cut Nova Maulidza (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the role of Indonesian language proficiency in shaping digital branding narratives for Micro, Small, and Medium Enterprises (MSMEs), particularly in connecting local cultural identity with the demands of the global market. The study employed a library research method by reviewing relevant academic journals and reference books related to the research topic. The findings indicate that effective Indonesian language proficiency is a strategic asset that enables MSME owners to build strong brand image and brand equity in the digital marketplace. However, MSMEs also face the challenge of balancing the use of Indonesian, which reflects local cultural values, with the adoption of global terminology commonly used in digital marketing. MSMEs that successfully integrate local linguistic strengths with adaptive digital communication strategies are more likely to enhance their competitiveness in the global market. Therefore, this study highlights the importance of improving Indonesian language competence while preserving local wisdom and remaining responsive to the evolving dynamics of international markets.